Borders in South Asia : interlinkages & challenges - Bhardwaj, Vinod (ed.); Sawant, Nandkumar N. (ed.); Saini, Manoj Kumar(ed.) (New Delhi G.B. Books, 2015)
Despite all natures of international borders prevailing in South Asia- open, restricted, semi-restricted, porous etc. intra regional movement is under practice as in other parts of the world. This book includes papers having vivid dimensions associated with inter-linkages, conflicts and challenges to management related to International Borders in South Asia.
Keywords: Territory, National; Boundaries; South Asia; India